Sonic agency : sound and emergent forms of resistance - LaBelle, Brandon (Goldsmiths Press sonics series., 2018)
"The book proposes a multi-dimensional understanding on sound and listening as capacities for challenging social and political structures of inequality and domination, supporting interpersonal exchange and modes of community-building based on empathy, care and compassion"--